Dacomitinib for Advanced Non-small Cell Lung Cancer Patients Harboring Major Uncommon EGFR Alterations: A Dual-Center, Single-Arm, Ambispective Cohort Study in China - Li, Hong-Shuai; Yang, Guang-Jian; Cai, Yi; Li, Jun-Ling; Xu, Hai-Yan; Zhang, Tao; Zhou, Li-Qiang; Wang, Yu-Ying; Wang, Jin-Liang; Hu, Xing-Sheng; Yan, Xiang; Wang, Yan (Frontiers in Pharmacology, 2022)
Objective: Dacomitinib has been approved for non-small-cell lung cancer (NSCLC) patients harboring classical epidermal growth factor receptor (EGFR) mutations; however, clinical evidence of its activity on major uncommon EGFR mutations is currently limited. Materials and methods: This was a dual-center, single-arm, ambispective cohort study in China. Patients with histologically confirmed metastatic or recurrent NSCLC harboring major uncommon EGFR mutations were eligible for the study. The objective response rate and disease control rate were determined by RECIST 1.1 every 1–2 months. Adverse events were assessed by CTCAE 5.0. Results: In total, 32 NSCLC patients were enrolled between July 2020 and January 2022, and 18 (56.3%) patients received dacomitinib as first-line therapy. Median age was 64 years, and 20 (62.5%) were female. The mutations identified were G719X (n = 24; 75%), followed by L861X (n = 10; 31.3%), and S768I (n = 8; 25%). In the first-line setting, 72.2% of patients (13/18) had a confirmed partial response and 100% (18/18) had disease control, and the median progression-free survival (PFS) and overall survival (OS) were unreached. In the whole cohort, 56.3% of patients (18/32) had a confirmed partial response and 90.6% (29/32) had disease control, and the median PFS was 10.3 months (95% confidence interval, 6.1–14.5) and the median OS was 36.5 months. Except for one case not available for brain re-evaluation, control of the intracranial metastases was observed in 13 patients (13/14, 92.9%). No grade 4–5 adverse events (AEs) occurred, but all patients had grade 1–2 AEs, and 12.5% (4/32) patients required a dosage reduction due to intolerable AEs. Conclusions: Dacomitinib demonstrated favorable activity with manageable toxicity in patients with NSCLC harboring major uncommon EGFR mutations.